(untitled) (Pesquisa Odontológica Brasileira, 2003)
Since in vitro pH-cycling models are widely used to study dental caries, they should allow evaluations of fluoride effect on early stages of caries development. Therefore, acid etching on enamel surface must be avoided, enabling surface microhardness (SMH) analysis. In the present study, the pH-cycling model originally described by Featherstone et al.9 (1986) was modified to preserve the enamel surface and to produce early carious lesions that could be evaluated using SMH and cross-sectional microhardness (CSMH) measurements. In order to validate this modified model, a dose-response evaluation with fluoride was made. Human enamel blocks with known SMH were submitted to such regimen with the following treatments: distilled deionized water (DDW; control) and solutions containing 70, 140 and 280 ppm F. Data from %SMH change and deltaZ (mineral loss) showed a statistically significant negative correlation between F concentration in treatment solutions and mineral loss. In conclusion, the modified pH-cycling model allowed the evaluation of changes on the outermost enamel layer during caries development, and a dose-response effect of fluoride reducing enamel demineralization was observed.